Beginning Windows Store Application DevelopmentHTML and JavaScript Edition - Isaacs, Scott. (Apress : Imprint: Apress, 2013)
Beginning WindowsStore Application Development HTML and JavaScript Edition introduces you to the Windows 8 modern app design paradigm and the new Windows 8 programming model developed around this paradigm. You'll learn to build rich, immersive applications designed to run on the many devices powered by Windows 8. The authors draw on their extensive practical experience to provide not only a comprehensive introduction to the model and its features, but guidance on best practices and a real-world sample application that you develop over the course of the book. Beginning WindowsStore Application Development HTML and JavaScript Edition also emphasizes how devices will be used and applications will be built in a world that has become far more connected. The book takes you beyond the syntax of any development languageand examines factors such as application design,user experience, social integration, and maintaining data and settings across multiple devices.